Adolescent cannabis experimentation and unemployment in young to mid-adulthood: Results from the French TEMPO Cohort study. (1st January 2022) - Barry, Katharine M.; Gomajee, Ramchandar; Kousignian, Isabelle; Bustamante, Joel José Herranz; Lakrout, Paula; Mary-Krause, Murielle; Melchior, Maria
Abstract: Background: France accounts for one of the highest levels of recreational cannabis use, with almost 40% of youth aged 17 reporting having experimented with cannabis. We investigated the impact of early cannabis experimentation (defined as first-time use ≤ 16 years) on future probability of unemployment in young to mid-adulthood using a longitudinal, community sample over the span of 9 years. Methods: Data were obtained from the French TEMPO Cohort study, set up in 2009 among young adults aged 22–25 years old. Participants who reported information on age of cannabis experimentation and employment status in at least one study wave (2009, 2011, 2015 and 2018) were included in the statistical analyses (N = 1487, 61.2% female). Results: In A-IPW-adjusted analyses, early cannabis experimenters (≤ 16 years) had 1.71 (95% CI: 1.46–2.02) times higher odds of experiencing unemployment compared to late cannabis experimenters (> 16 years) and 2.40 (95% CI: 2.00 – 2.88) times higher odds of experiencing unemployment compared to non-experimenters. Late cannabis experimenters experienced 1.39 (95% CI: 1.17–1.68) times higher odds of being unemployed compared to non-experimenters, and early cannabis experimenters experienced 3.84 (95%CI: 2.73–5.42) times higher odds of experiencing long-term unemployment (defined as unemployed at least twice) compared to non-experimenters. Conclusions: Participants who ever used cannabis, especially at or before the age of 16, had higher odds of experiencing unemployment, even when accounting for many psychological, academic and family characteristics which preceded cannabis initiation. Highlights: The direct role of early cannabis experimentation on later employment outcomes is still not fully known. Cannabis experimentation during adolescence is associated with unemployment in mid-to-young adulthood. Early cannabis experimenters experience higher odds of unemployment compared to late cannabis initiators and non-users.